Analysis of association between posterior crossbite, median line deviation and facial asymmetry - Santos, R. R. [UNESP]; Garbin, Artênio José Isper [UNESP]; Saliba, O. [UNESP]; Garbin, C. A. S. [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2014)
Facial asymmetry is a common human characteristic and can occur on many levels, originate of genetic factors, and can be caused by traumas or due to cross bite and/or muscular disability. The aim of this study was to evaluate the relation between posterior crossbite, median line deviation and facial asymmetry. For this study 70 children aged between 3 and 10 years-old were examined and photographed. Using Microsoft Office Power Point 2007, horizontal lines and one vertical line on median line were drawn, to subjectively analyze facial discrepancies. In relation to overjet, the majority of children (78.6%) showed normal relation, followed by high overjet (17.1%), anterior crossbite (4.3%). In relation to overbite, the majority of children (60%) showed normal relation, 27.1% anterior opened bite (negative overbite), and 12.9% showed high overbite. Posterior crossbite was present in 27.1% of children. Among them, 68.4% showed unilateral crossbite on right side, 21.1% bilateral crossbite and 10.5% unilateral crossbite on left side. The relation between posterior crossbite and facial asymmetry, according to Fisher´s Exact Test (p=0.0970), there was no statistically significant association. In relation to median line, the association was statistically significant with posterior crossbite (p=0.0109) and with facial asymmetry (p=0.0310). There was association between posterior crossbite and median line deviation. There was no association between posterior crossbite and facial asymmetry.

La asimetría facial es una característica humana común que puede ocurrir en diferentes niveles, originarse por factores genéticos, ser causada por traumas o mordida cruzada como resultado o discapacidad muscular. El objetivo de este estudio fue evaluar la relación entre la mordida cruzada posterior, desviación de la línea mediana y asimetría facial. Fueron evaluados 70 niños entre 3 y 10 años de edad mediante examen clínico y fotográfico. Utilizando Microsoft Power Point Office 2007, se dibujaron líneas horizontales y una línea vertical en la línea mediana, para analizar subjetivamente las diferencias faciales. En relación con el resalte, la mayoría de los niños (78,6%) mostró relación normal, seguido por un resalte aumentado (17,1%) y mordida cruzada anterior (4,3%). En relación con la sobremordida, la mayoría de los niños (60%) mostró relación normal, 27,1% una mordida abierta anterior (sobremordida negativa) y 12,9% mostró una sobremordida aumentada. La mordida cruzada posterior estuvo presente en 27,1% de los niños. Entre ellos, el 68,4% presentaba mordida cruzada unilateral del lado derecho, 21,1% mordida cruzada bilateral y el 10,5% mordida cruzada unilateral en el lado izquierdo. No hubo asociación estadísticamente significativa entre la mordida cruzada posterior y asimetría facial según la prueba exacta de Fisher (p=0,0970). En relación a la línea mediana, se observo una asociación estadísticamente significativa entre mordida cruzada posterior (p = 0,0109) y asimetría facial (p=0,0310). Existe asociación entre la mordida cruzada posterior y la desviación de línea mediana. No hubo asociación entre la mordida cruzada posterior y asimetría facial.
Análisis de la asociación entre mordida cruzada posterior, desviación de la línea mediana y asimetría facial
Keywords: Facial asymmetry; Crossbite; Malocclusion; Orthodontics; Asimetría facial; Mordida cruzada; Maloclusión; Ortodoncia